With Gratitude from RHiME: Reviewers 2024 - RHiME, Editor (Research and Humanities in Medical Education, 2025)
The Editorial Board of RHiME would like to thank the following reviewers for their outstanding contribution to the work of the journal. Without their dedication and the time they devoted to the evaluation of submissions made to RHiME, it would have been impossible to maintain the standard of the journal. Ahmad Ozair Arjun Ravishankar Jarina Begum Julia Patrick Engkasan Munira Hirkani Navjeevan Singh P Ravi Shankar Pranab Chatterjee Prateek Suresh Harne Rajat Thawani Satendra Singh Smriti Rana Sonia Singh Kharay Tanvi Jha William Wilson